Turkish validity and reliability of Multidimensional Health Locus of Control Scale Form A. Issue 5 (12th December 2019) - Güzel, Aysun; Turan, Sevgi; Üner, Sarp
Abstract: Aim: The aim of this study was to assess the validity and reliability of the Turkish version of Multidimensional Health Locus of Control Scale Form A. Methods: The research is a methodological instrument validation study, and the study sample consisted of 275 participants. The data collection phase of the study was completed between 15 July and 15 September 2016. The study used data collection tools including a Personal Information Form, the Multidimensional Health Locus of Control Scale Form A, and the Internal‐External Locus of Control Scale. Data on sociodemographic variables are presented as percentages and means. Confirmatory factor analysis and correlation analyses were used. Results: The Cronbach α values of the subdimensions of the Multidimensional Health Locus of Control Scale Form A were determined as acceptable for the internal control, the chance, and powerful other subscales. The confirmatory factor analysis showed acceptable values and acceptable fit for the model fit statistics. Conclusion: The Turkish version of Multidimensional Health Locus of Control Scale Form A was accepted as valid and reliable. SUMMARY STATEMENT: What is already known about this topic? The Multidimensional Health Locus of Control Scale is a measurement tool that measures an individual's belief regarding control over their disease or health conditions. The scale consists of three forms: Forms A and B are used to measure the locus of health control in the general population and healthy individuals, while Form C is used in individuals with chronic disease. Form A is used frequently across the world, and validity and reliability studies have been conducted by many researchers. Form A is also frequently used in studies in Turkey, but no study could be found regarding its reliability and validity for Turkey. What this paper adds? The Turkish version of the Multidimensional Health Locus of Control Form A was determined to be valid and reliable for people aged between 20 and 69 years old. It can be used to measure the health locus of control of individuals within this age range. Form A can be used in the measurement of the health locus of control in the 20 to 69 age group in the general population and in patients with physical or mental illness, in patients' relatives, and in healthy people in this age group. The implications of this paper: In order to develop successful policies on health‐related issues and conduct successful interventions, the attributions made by individuals about their locus of control, whether internal, governed by chance, or determined by powerful others are important. Measuring locus of control increases success in planning and implementing of health‐care education for adolescents, university students, those with chronic illnesses, caregivers, rural workers, and elderly people. It is important for nurses to know individuals' health loci of control when caring for patients. All the research has emphasized that the ability of individuals and groups to attain a stated goal is improved when they believe they have internal control. Further research is needed to clarify how the culture and social structure of different countries affect individuals' health loci of control.